2022
DOI: 10.3889/oamjms.2022.8116
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Clinical Practice Experience during the COVID-19 Pandemic: A Qualitative Study

Abstract: BACKGROUND: The COVID-19 pandemic is putting clinical practice in all nursing schools to the challenge. While students should be cautious of infection, they still need to practice in a hospital setting. AIM: The purpose of this study is to gain insight into students’ clinical experiences during the COVID-19 pandemic. METHODS: This study employed a qualitative methodology and a phenomenological approach. A purposive sampling technique was used to recruit seven clinical nursing students. We conducted semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 20 publications
0
12
0
10
Order By: Relevance
“…In facing such an emerging infectious disease, nursing students’ high fear levels and fear of losing their lives were understandable, as they were beginners in the healthcare profession who did not have experience handling similar situations. The literature showed that the students’ fear of COVID-19 was predominantly related to an insufficient supply of personal protective equipment (PPE), a lack of disaster knowledge and competency in responding to the pandemic [ 48 , 49 ], and the perceived risk of getting infected and transmitting the disease to others or their families [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In facing such an emerging infectious disease, nursing students’ high fear levels and fear of losing their lives were understandable, as they were beginners in the healthcare profession who did not have experience handling similar situations. The literature showed that the students’ fear of COVID-19 was predominantly related to an insufficient supply of personal protective equipment (PPE), a lack of disaster knowledge and competency in responding to the pandemic [ 48 , 49 ], and the perceived risk of getting infected and transmitting the disease to others or their families [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this study found insignificant negative correlations between the FCV-19S and DASS-21, the literature indicated that inadequate PPE supply and fear of getting infected significantly correlated with a high anxiety level among nursing students [ 51 ]. The students appreciated the opportunity to care for COVID-19 patients in hospitals; however, they were also stressed and afraid [ 48 ]. Nursing students thought they were unprepared and incapable of handling complicated clinical situations during the pandemic [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if clinical site practice is fully resumed in the post-corona era, it is worth using alternative clinical practice as a supplement. Even though there are learning goals that students must achieve in the clinical setting, it is not possible to experience and learn everything during clinical practice [ 15 ]. A previous study [ 2 ] recommended including simulation in the clinical practice curriculum to reduce the instability of clinical practice and provide stable, practical education.…”
Section: Discussionmentioning
confidence: 99%
“…Publications on domestic and foreign qualitative research methods related to the clinical practice of nursing students in the current COVID-19 situation were published on clinical field practice experience [ 13 , 14 , 15 , 16 ], online clinical practice experience [ 4 , 17 , 18 ], virtual reality-based simulation clinical practice experience in one subject [ 6 ], online clinical practice and in-school clinical practice experience [ 19 ]. Clinical practice experience in clinical field practice or alternative clinical practices was limited in each partial aspect.…”
Section: Introductionmentioning
confidence: 99%